Two different varieties of Staphylococcus aureus based on the correlation between antigenic structure, phage pattern, antibiotic pattern and virulence - Torres Pereira, A. (International Journal of Systematic and Evolutionary Microbiology, 1965)
SUMMARY The majority of recent isolates of Staphylococcus aureus can be separated into two varieties and these may correspond to the original antigenic forms of Cowan’s serotypes I and III. The most common variety has antigen 17 or I as a surface antigen and is lysed by serological group B phages; it may contain serological group A prophages and is usually tetracycline sensitive. It is probably more virulent (particularly in the 17+ form) than the second variety which possesses antigen 13 or 3, and is lysed by serological group A phages and may contain B prophages. It is usually tetracycline resistant.